Current Epidemiology and Outcome of Infective Endocarditis: A Multicenter, Prospective, Cohort Study. Issue 43 (October 2015) - Muñoz, Patricia; Kestler, Martha; De Alarcon, Arístides; Miro, José María; Bermejo, Javier; Rodríguez-Abella, Hugo; Fariñas, Maria Carmen; Cobo Belaustegui, Manuel; Mestres, Carlos; Llinares, Pedro; Goenaga, Miguel; Navas, Enrique; et al.
Abstract : Abstract: The aim of the study was to describe the epidemiologic and clinical characteristics and identify the risk factors of short-term and 1-year mortality in a recent cohort of patients with infective endocarditis (IE). From January 2008, multidisciplinary teams have prospectively collected all consecutive cases of IE, diagnosed according to the Duke criteria, in 25 Spanish hospitals. Overall, 1804 patients were diagnosed. The median age was 69 years (interquartile range, 55–77), 68.0% were men, and 37.1% of the cases were nosocomial or health care-related IE. Gram-positive microorganisms accounted for 79.3% of the episodes, followed by Gram-negative (5.2%), fungi (2.4%), anaerobes (0.9%), polymicrobial infections (1.9%), and unknown etiology (9.1%). Heart surgery was performed in 44.2%, and in-hospital mortality was 28.8%. Risk factors for in-hospital mortality were age, previous heart surgery, cerebrovascular disease, atrial fibrillation, Staphylococcus or Candida etiology, intracardiac complications, heart failure, and septic shock. The 1-year independent risk factors for mortality were age (odds ratio [OR], 1.02), neoplasia (OR, 2.46), renal insufficiency (OR, 1.59), and heart failure (OR, 4.42). Surgery was an independent protective factor for 1-year mortality (OR, 0.44). IE remains a severe disease with a high rate of in-hospital (28.9%) and 1-year mortality (11.2%). Surgery was the only intervention that significantly reduced 1-year mortality.